2008
DOI: 10.1080/01459740802427729
|View full text |Cite
|
Sign up to set email alerts
|

Nerves as Embodied Metaphor in the Canada/Mexico Seasonal Agricultural Workers Program

Abstract: This article examines nerves among participants in the Canada/Mexico Seasonal Agricultural Workers Program (C/MSAWP). Based on in-depth interviews with 30 Mexican farm workers in southwestern Ontario, we demonstrate that nerves embodies the distress of economic need, relative powerlessness, and the contradictions inherent in the C/MSAWP that result in various life's lesions. We also explore their use of the nerves idiom as an embodied metaphor for their awareness of the breakdown in self/society relations and,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 25 publications
1
16
0
Order By: Relevance
“…In particular, there was resonance with topics like “the lack of transportation”, “living on the property of employers”, and “language and literacy barriers”. As previously reported, these make MFWs dependent on their employers for private matters [1,9,16,19]. Cognizant of these barriers, more than half of the employers in our study displayed a strong sense of responsibility and care for their workers, providing them with support beyond the responsibilities of the work contract.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…In particular, there was resonance with topics like “the lack of transportation”, “living on the property of employers”, and “language and literacy barriers”. As previously reported, these make MFWs dependent on their employers for private matters [1,9,16,19]. Cognizant of these barriers, more than half of the employers in our study displayed a strong sense of responsibility and care for their workers, providing them with support beyond the responsibilities of the work contract.…”
Section: Discussionsupporting
confidence: 63%
“…While the MFWs’ dependence on their employers is widely known from previous studies [15,16,18], we found that employers are also heavily dependent on the MFWs for the expansion or even the survival of their business in a globally competitive market. As described by McLaughlin [15], MFWs were seen as the “backbone” of the farms by all our research participants.…”
Section: Discussionmentioning
confidence: 61%
“…The expression of ''nerves'' among migrant farmworkers as an embodiment of distress over conditions of economic need and powerlessness was associated with migrant farm work in Canada [Mysyk et al, 2008;England et al, 2007]. Farmworkers work in environments where they have little control, are pressured by piece-work wages and the demands of completing farm work within constraints of timing due to weather and market and are required to work long hours without adequate breaks, all of which create high stress levels [Hiott et al, 2008].…”
Section: Obesity and Occupational Health Among Farmworkersmentioning
confidence: 99%
“…16 Mental health disorders, especially depression and anxiety, are another major issue among migrants. Qualitative studies involving 30 migrant farm workers in Ontario 17 and 75 in the United States 18 reported numerous themes that contributed to psychological malady, including poverty, discrimination, living and working conditions that are unpredictable, difficult or rigid, and cultural and familial dislocation.…”
Section: -18mentioning
confidence: 99%